Induction of Fertile Estrus in Bitches using Equine Chorionic Gonadotropine (eCG) and Human Chorionic Gonadotropine (hCG) - Al-Hamedawi, Talib M. (The Iraqi Journal of Veterinary Medicine, 2013)
Eighteen (18) anestrous bitches aged 3-6 years were used in this study. They were diagnosed clinically by external and vaginal examination and the bitches were divided randomly into three equal groups (6 bitches). The 1st group were treated I/M with 20 IU eCG / bitch for 6 days with single injection and 150 IU of hCG hormone /Bitch on day 7 . The 2nd group were treated I/M with 30 IU eCG / bitch for 6 days with single injection and 150 IU of hCG hormone /bitch on day 7, and the 3rd group were treated I/M with 40 IU eCG / bitch for 6 days with single injection and 150 IU of hCG hormone /bitch on day 7. Results showed that the number responded (show proestrus bleeding) were 83.3%, 100% and 83, 3% for the 1st,2nd and 3rd group respectively. The mean duration response from the beginning of treatment to onset of proestrus bleeding were 15.23 ± 2.36, 14.83± 2.43 and 14.16 ±2.58 day respectively .1st and 3rd group recorded significantly P<0.01 higher in response to treatment 1st group recorded significantly higher (P<0.01) compared with 2nd and 3rd group in duration of response. The conception rate was 80% (4/5), 83.3%(5/6) and 60%(3/5) in 1st, 2nd and 3rd group respectively were the 1st and 2nd group recorded higher significant compared with 3rd group. The dystocia parturition was appeared 8.4 % (1/12) from total animals, while the percentage of live newborn (whelps) was 29 (76.3%) and dead 9 (23.7%). In conclusion that the using gonadotrophic hormones (eCG and hCG) have an positive effect of induction the estrus on anestrous bitches.